A systematic review of epidemiological studies investigating risk factors for work-related road traffic crashes and injuries. Issue 1 (1st February 2008) - Robb, G; Sultana, S; Ameratunga, S; Jackson, R
Abstract : Objective: To critically appraise the published evidence for risk factors for injuries and deaths relating to work-related road traffic crashes. Design: Systematic review. Data sources: Electronic databases searched included Medline, EMBASE, PsycINFO, Transport database, and the Australian Transport and Road Index (ATRI) database. Additional searches included websites of relevant organizations, reference lists of included studies, and issues of major injury journals published within the past 5 years. Inclusion criteria: Studies were included if they investigated work-related traffic crashes or related injuries or deaths as the outcome, measured any potential risk factor for work-related road traffic crash as an exposure, included a relevant comparison group, and were written in English. Methods: Included studies were critically appraised using the GATE-lite critical appraisal form (www.epiq.co.nz ). Meta-analysis was not attempted because of the heterogeneity of the included studies. Findings: Of 25 studies identified, three of four robust (case–control and case-crossover) studies found an increased injury risk (i) among workers after extended shifts, (ii) for tractor-trailers with brake and steering defects, and (iii) for "double configuration" trucks. The fourth study showed that alcohol and drug use were not risk factors in an industry with a random testing policy. The best cross-sectional studies showed associations between injury and sleepiness, time spent driving, occupational stress, non-insulin-dependent uncomplicated diabetes, and use of narcotics and antihistamines. Conclusions: Modifiable behavioral and vehicle-related risk factors are likely to contribute to work-related traffic injury. Fatigue and sleepiness—the most commonly researched topics—were consistently associated with increased risk.